A inexistência de ordem V-S no português brasileiro (Revista de Estudos da Linguagem, 2003)
The paper examines the occurrence of post-verbal DP in inacusativesentences, which is traditionally treated as the V-S Order and stillpresented in BP. Assuming the Minimalist program (CHOMSKY,1995) and ZUBIZARRETTA (1995), this paper proposes that in BP:i) the sentences treated, in the literature, as case of V-S Order areconstructed based on a Numeration containing [-accusative] verband an element specified by the [+F] trace, from which results anApresentative structure; ii) in BP the [-accusative] DP generated inthe inner position of V and specified with [+F] feature stays in thatposition, where it receives the main stress of the sentence so that itis a Nominative Object; iii) the inacusative sentences, which aretraditionally regarded as having the V-S Order, leave the SVOstructure. Therefore there is no possibity of treating them as theV-S Order in BP.